PENAMBAHAN PROGRAM AKTIVITAS UNTUK MENGEMBALIKAN KUALITAS PLACE PADA MALL PLUIT VILLAGE - Wijaya, Daniel; Carina, Nina (Jurusan Arsitektur dan Perencanaan, 2024)
Pluit Village Mall, which was established in 1996 and has an area of 86,691 square meters, used to be the main entertainment center in the Pluit area. However, the number of visitors continues to decrease every year. Pluit Village Mall did not anticipate the changing times that resulted in changing activity patterns. The facilities remain the same, the architectural style lags and the lack of innovation makes the people of Pluit abandon this mall. To determine the factors that caused the decline in the number of visitors at Pluit Village Mall, the author used comparative, qualitative, and direct observation research methods. Data collected from various sources, including journals and the internet, were compared with current theoretical findings. The results of the comparison show that additional buildings that offer a variety of new facilities that are different from the old ones are needed to re-attract visitors and improve the quality of Pluit Village Mall. A